Optimizaton of Cationic Lipid Mediated Transfection of pEGFP-c1 and pJ-EPO Plasmids in Chinese Hamster Ovary (CHO) Cells Attached Culture for Transient and Stable Recombinant Human Erythropoietin (rhEPO) Expression - Septisetyani, Endah Puji; Kusumawati, Arizah; Santoso, Adi (Annales Bogorienses, 2015)
Cationic lipid is one of transfection agents which show high efficiency and low cytotoxicity. The transfection efficiencies can be varied depending upon the type or amount of cationic lipids, the cell line or DNA plasmid being used for transfection. The purpose of this study was to find optimal condition for transfection of CHO-K1 and CHO-S cells with pJ-EPO plasmid (containing human erythropoietin/ hEPO gene) compared with pEGFP-c1 plasmid (containing green fluorescence protein/gfp gene) by cationic lipid Lipofectamin 2000TM (lipofectamin) to generate stable transfectant expressing recombinant human erythropoietin (rhEPO). Optimization was carried out regarding the amount of lipofectamin, DNA concentration, and concentration of antibiotic Geneticin (G418) for selection of stable transfectants. By using standard amount of lipofectamin (10 μl/well) in 6-well plate, highest expression level of green fluorescent protein (GFP) was shown after transfection of CHO-K1 cells with 3 μg/well pEGFP-c1 while highest expression level of rhEPO was observed after transfection of CHO-K1 cells with 6, 8, or 10 μg/well pJ-EPO plasmid. The data also indicated that optimal transfection conditions of CHOK1 and CHO-S cells with pJ-EPO were shown with the use of 4 μg/well DNA in combination with 15 μl lipofectamin. Concentration of G418 used during cells selection also affected the expression where strongest rhEPO expression was shown at 750 ng/μl G418 concentration. Similar to GFP expression profile, rhEPO signal was detected very low during selection process sbased on Western blot data at day 9. Stronger rhEPO signal was observed after day 20 when the stable transfectants have been obtained.